THE STEAM PLATFORM ECONOMY: CAPITALISING FROM PLAYER-DRIVEN ECONOMIES ON THE INTERNET. - Thorhauge, Anne Mette (AoIR Selected Papers of Internet Research, 2020)
With this paper I aim to analyse and discuss the Steam game platform in a platform economic perspective. I will argue that Steam represents a special type of platform economy due to its roots in gaming economies: Steam’s platform economy can be seen as a specific way of capitalising on the player-driven economies that arise within and beyond key game titles offered on the platform. The API offered to third party developers on Steams websites can be described as a ‘palette of monetization strategies’ that run from simple retail models in the game store, over various ways of integrating user generated content in the Steam Workshop to the prospects of harnessing and capitalising from players’ economic action in the Community market. A look some of the most-played games titles shows that this gives rise to a variety of diverse monetization strategies. Many of those monetization strategies move beyond advertising and the attention economy, making players trades another potential source of income. In all cases, of course, Steam gets its share.